Writing web logs in the ESL Classroom: a study of student perceptions and the technology acceptance model / Mah Boon Yih and Er Ann Nah - Mah, Boon Yih (ACRULeT, Faculty of Education & UiTM Press, 2009)
The web log is an exceptionally valuable tool for the teaching of second language writing, particularly written communication skills (Johnson, 2004; Wu, 2005). More and more international educators have applied this easy-to-use technology to classroom instruction and language learning (Campbell, 2003; Johnson, 2004). However, what is largely unknown is Malaysian students’ reaction to writing web logs in English as a Second Language (ESL) classrooms. Therefore, this study aims to investigate the perception of writing web logs among Universiti Teknologi MARA (UiTM) HM115 diploma students who took the BEL311 English course in their third semester based on the three Technology Acceptance Model (TAM) variables. Specifically, the study sought to identify whether the two TAM determinants,Perceived Ease of Use (PEOU) and Perceived Usefulness (PU), affected the students’ behavioural intention (BI) to use web logs for specific writing tasks. This study employed Davis’s TAM (1989) and its questionnaire-based measurement instrument and three hypotheses were formulated based on the objectives of the study. The pilot test’s result confirmed the reliability of the modified TAM-based questionnaire. The findings showed that students accept writing web logs as a classroom activity since they perceived online journals to be more useful rather than easy to use. Additionally, the findings revealed that TAM can be used to diagnose and interpret the attitude of new technology users and most importantly, PEOU, PU, and BI were positively and highly correlated at a significant level. These results did not reject the three proposed hypotheses.